2013
DOI: 10.1128/aem.01028-13
|View full text |Cite
|
Sign up to set email alerts
|

Increased Water Activity Reduces the Thermal Resistance of Salmonella enterica in Peanut Butter

Abstract: c Increased water activity in peanut butter significantly (P < 0.05) reduced the heat resistance of desiccation-stressed Salmonella enterica serotypes treated at 90°C. The difference in thermal resistance was less notable when strains were treated at 126°C. Using scanning electron microscopy, we observed minor morphological changes of S. enterica cells resulting from desiccation and rehydration processes in peanut oil. Salmonellosis outbreaks linked to contaminated peanut butter products have brought worldwide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(42 citation statements)
references
References 23 publications
(26 reference statements)
1
39
0
2
Order By: Relevance
“…In this study, we used 25 g of peanut butter which is not a suitable size for industrial processing. Other research studies which confirmed the effect of conventional heating on peanut butter pasteurization reported that less than 1 min of come-up time was required for samples to reach 90 C. But these studies used small amounts of peanut butter (Li et al, 2014;Ma et al, 2009) and flattened peanut butter samples to increase heat transfer (He et al, 2011(He et al, , 2013Li et al, 2014;Ma et al, 2009). We used a 915 MHz microwave which provided much greater penetration depth than a 2450 MHz microwave.…”
Section: Time-temperature Profiles Of Peanut Butter During 915 Mhz MImentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, we used 25 g of peanut butter which is not a suitable size for industrial processing. Other research studies which confirmed the effect of conventional heating on peanut butter pasteurization reported that less than 1 min of come-up time was required for samples to reach 90 C. But these studies used small amounts of peanut butter (Li et al, 2014;Ma et al, 2009) and flattened peanut butter samples to increase heat transfer (He et al, 2011(He et al, , 2013Li et al, 2014;Ma et al, 2009). We used a 915 MHz microwave which provided much greater penetration depth than a 2450 MHz microwave.…”
Section: Time-temperature Profiles Of Peanut Butter During 915 Mhz MImentioning
confidence: 99%
“…This is due to the increase in the consumption of peanut butter from 1999 to 2008 while peanut candy and snack consumption has not (USDA, 2010). Peanut butter has low a w (less than 0.35) which precludes the growth of foodborne pathogens (He et al, 2013). But unfortunately, multistate outbreaks caused by peanut butter have been reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A great example is the Salmonella outbreak in peanut butter. It was a shocking evidence to discover that Salmonella had higher heat tolerance (Shachar and Yaron, 2006;He et al, 2013) in low water activity and high-fat content food. 600 cases were reported in the Salmonella outbreak in peanut butter (Crum-Cianflone, 2008).…”
Section: Emerging Foodborne Pathogensmentioning
confidence: 99%
“…Thermal processing has been evaluated as an option for inactivating Salmonella spp. in peanut butters, spreads, and pastes using conventional thermal inactivation study approaches (He et al, ; He, Guo, Yang, Tortorello, & Zhang, ; Keller et al, ; Li, Huang, & Chen, ; Shachar & Yaron, ). Time and temperature were consistently verified as critical parameters; however, heat resistance of Salmonella spp.…”
Section: Introductionmentioning
confidence: 99%